Predation and Mergers: Is Merger Law Counterproductive? - Lars Persson (The Research Institute of Industrial Economics (IUI), 1999)
This paper studies the interaction between the incentives for predation and mergers. I show that the incentive for predation in an oligopoly is limited by the subsequent competition for the prey. This bidding competition is expecially fierce when the prey's assets exert strong negative externalities on rivals. Firms may therefore prefer to predate to destroy the prey's assets, rather than just its financial viability. The paper also demonstrates that predation may be preferred to an immediate merger for two reasons. First, by predating, firms may share the costs of eliminating a rival and circumvent the free-riding problem associated with mergers, and second, destructive predation helps firms avoid the bidding competition. It is also shown that a restrictive merger policy may be counterproductive, since it may increase the incentives for predation by helping predators avoid the bidding competition. Moreover, the incentive for predation under the US failing firm defense might be even stronger, since it allows mergers bu limits the bidding competition.
Keywords: K21; L12; L41; 330; Mergers; Predation; Merger law; Failing firm defense; Fusion; Verdrängungswettbewerb; Wettbewerbsrecht; Fusionskontrolle; Oligopol; Theorie